2006
DOI: 10.1007/s10722-004-1337-7
|View full text |Cite
|
Sign up to set email alerts
|

Total Protein and Amino acid Compositions in the Acorns of Turkish Quercus L. Taxa

Abstract: Total protein content and level of 14 amino acid in mature acorns of 20 Quercus taxa from Turkey were studied. The range of total protein amounts between 2.75 and 8.44% were detected among taxa. Similar values in related species and variety level were observed. The amino acid profiles for each taxon were characteristically different and high variability of individual amino acid concentration was present at variety, subspecies and species levels. Different amino acid concentrations, relative percentages and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…This result agrees with the results reported by (Özcan, 2006 andLopes et al, 2005) who found that the oil content of some species of acorn ranged between 3.8 and 9.1%. This indicates that the oil content of these acorn species is low for commercial production as cooking or frying oils.…”
Section: Resultssupporting
confidence: 93%
“…This result agrees with the results reported by (Özcan, 2006 andLopes et al, 2005) who found that the oil content of some species of acorn ranged between 3.8 and 9.1%. This indicates that the oil content of these acorn species is low for commercial production as cooking or frying oils.…”
Section: Resultssupporting
confidence: 93%
“…This is not to say that the internal and even leaf surface composition of plant primary metabolites cannot be genotype-specific (see Yeoh et al 1984;Soldaat et al 1996;Özcan 2006). Plant secondary metabolites are thought to determine host specificity through their tendencies to be perceived at distance from the source (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Due to high variability of genus, Quercus acorns differ in chemical composition, depending on the species. It could be generally said that 31-55 % of their mass is composed by starch, 2.75-8.44 % protein (with advantageous amino acid composition, and high content of essential amino acids, proper especially for adults), 0.7-9 % fat (although in some species of Quercus Erthrobalanus spp., i.e., black and red oak group, it may exceed 31 %) [11,[15][16][17]. Oil present in acorns has a taste comparable to olive oil and contains high levels of unsaturated fatty acids (even above 80 %), mostly oleic and linoleic acids, 10.2-65 % and 17.6-49.1 %, respectively [15,18].…”
Section: Introductionmentioning
confidence: 99%